Benefits of Early Diagnosis and Early Management Helps in Speech and Language Development in Hearing Impaired Children (Medical Forum Monthly, 2024)
Objective: The objective of this study is to determine the age of diagnosis of hearing impairment in children and outcome of early management in linguistic acquisition in hearing impaired children.Study Design: A descriptive cross-sectional study in cross section population.Place and Duration of Study: This study was conducted at the Otorhinolaryngology department of Abbasi Shaheed Hospital. This study was conducted from January 2022 to June 2023.Methods: Detail history and complete examination was done. Relevant investigations were performed. After fulfill the selection criteria, patients advised hearing amplification device and speech therapy. Patients called for follow-up and observe language development.Results: Total number of patients selected for this study was 105 patients. Female were 57 (54%). Female male ratio was 1.18. 38 (36%) children were between the ages of 2-3 years came first time in ENT department with complaining of hearing impairment followed by 1-2 years 33 (31%). 59 (56%) patients showed improvement in speech and language development while 46 (43.8%) patients showed poor performance in development of speech and language. Highest frequency of improvement in language development was observed between ages of 0-1 years 15 (78.9%) patients out of 19 patients. Poor performance in development of speech and language was noted between 3-4 years 2 (13.3%) out of 15 patients.Conclusion: Early diagnosis of hearing impairment and appropriate treatment observed good result in language development